Response to Acierno's comments on Wong and Waite, "Elder mistreatment predicts later physical and psychological health: Results from a national longitudinal study". Issue 2 (27th May 2017) - Wong, Jaclyn S.; Waite, Linda J.
ABSTRACT: We respond to Dr. Acierno's concerns about the measurement of elder mistreatment and social support in the National Social Life, Health, and Aging Project. We made our analytic decisions carefully and conducted systematic robustness checks and believe our findings are theoretically important.